Effect of thermal rectification on colors of Eucalyptus saligna and Pinus caribaea woods - Sodero Martins Pincell, Ana Lúcia Piedade; de Moura, Luiz Fernando; Brito, José Otávio (Maderas. Ciencia y Tecnología, 2025)
Eucalyptus saligna and Pinus caribaea var. hondurensis woods underwent a variety of thermal rectifi cation treatments (from 120ºC to 180ºC) to evaluate the effect of heating on their colorimetric properties. The following color parameters were measured: lightness (L), a* coordinate (green-red coordinate), b* coordinate (blue-yellow coordinate), saturation (C), and tonality angle (H). This study demonstrates that thermal rectifi cation can be regarded as a tool for adding value to wood through color modifi cation by heating. Results also suggest that thermal rectifi cation might be a tool for homogenizing wood tonality and reddish color between species. Both tested species have shown very distinct colorimetric behaviors as a function of thermal treatments. The conifer was more resistant to thermal darkening than the hardwood while exposed to temperatures below 160oC. The green-red coordinate (a*) and the tonality angle (H) tended to be homogenized for both species, as they decreased in eucalyptus, and increased in pinus, as a function of heating. The effect of wood heating on the blue-yellow coordinate (b*), saturation (C), and tonality angle (H) was likely to be opposite between both tested species.